Informed Consent as a Litigation Strategy in the Field of Aesthetic Surgery: An Analysis Based on Court Precedents - Park, Bo Young (Arch Plast Surg, 2016)
BACKGROUND: In an increasing number of lawsuits doctors lose, despite providing preoperative patient education, because of failure to prove informed consent. We analyzed judicial precedents associated with insufficient informed consent to identify judicial factors and trends related to aesthetic surgery medical litigation. METHODS: We collected data from civil trials between 1995 and 2015 that were related to aesthetic surgery and resulted in findings of insufficient informed consent. Based on these data, we analyzed the lawsuits, including the distribution of surgeries, dissatisfactions, litigation expenses, and relationship to informed consent. RESULTS: Cases were found involving the following types of surgery: facial rejuvenation (38 cases), facial contouring surgery (27 cases), mammoplasty (16 cases), blepharoplasty (29 cases), rhinoplasty (21 cases), body-contouring surgery (15 cases), and breast reconstruction (2 cases). Common reasons for postoperative dissatisfaction were deformities (22%), scars (17%), asymmetry (14%), and infections (6%). Most of the malpractice lawsuits occurred in Seoul (population 10 million people; 54% of total plastic surgeons) and in primary-level local clinics (113 cases, 82.5%). In cases in which only invalid informed consent was recognized, the average amount of consolation money was KRW 9,107,143 (USD 8438). In cases in which both violation of non-malfeasance and invalid informed consent were recognized, the average amount of consolation money was KRW 12,741,857 (USD 11,806), corresponding to 38.6% of the amount of the judgment. CONCLUSIONS: Surgeons should pay special attention to obtaining informed consent, because it is a double-edged sword; it has clinical purposes for doctors and patients but may also be a litigation strategy for lawyers.